High Confident Evaluation for Smart City Services - Sheng, Hao; Zhang, Yang; Wang, Wei; Shan, Zhiguang; Fang, Yufei; Lyu, Weifeng; Xiong, Zhang (Frontiers in Environmental Science, 2022)
This study aims to analyze massive data in cities through data vitalization, and quantitatively evaluate smart city services, so as to promote the construction and development of smart cities. Due to the great difference between cities, a single evaluation method cannot accurately describe the development of a city. In this study, we classify cities by multiple labels according to various bases to give cities comprehensive description. Then, a Multi-level Service Evaluation System (MSES) is introduced. It considers individual weights to cities with different characteristics and evaluates the smart city services from different aspects. In addition to putting forward the iterative development of smart city services, a Maturity Model-based Service Evaluation (MMSE) framework is proposed based on the evaluation results of the MSES. It constructs a standardized and high confident evaluation framework to analyze the current state of cities and make feedback to the government policies. Finally, we take 10 cities in China to demonstrate the effectiveness of MMSE during the development of smart city services.